Retrograde signals control dynamic changes to the chromatin state at photosynthesis-associated loci - Marti Quevedo; Ivona Kubalová; Alexis Brun; Luis Cervela-Cardona; Elena Monte; Åsa Strand (Nature Communications)
Abstract Retrograde signalling networks originating in the organelles dictate nuclear gene expression and are essential for control and regulation of cellular energy metabolism. We investigate whether such plastid retrograde signals control nuclear gene expression by altering the chromatin state during the establishment of photosynthetic function in response to light. An Arabidopsis thaliana cell culture provides the required temporal resolution to map four histone modifications during the greening process. We uncover sequential and distinct epigenetic reprogramming events where an epigenetic switch from a histone methylation to an acetylation at photosynthesis-associated loci is dependent on a plastid retrograde signal. The transcription factors VIVIPAROUS1/ABI3-LIKE (VAL1), RELATIVE OF EARLY FLOWERING 6 (REF6) and GOLDEN2-LIKE FACTOR1/2 (GLKs) are linked to the H3K27ac deposition at photosynthesis associated loci that precedes full activation of the photosynthesis genes. Our work demonstrates that retrograde signals play a role in the epigenetic reprogramming essential to the establishment of photosynthesis in plant cells.